Moderate Photoinhibition of Photosystem II Significantly Affects Linear Electron Flow in the Shade-Demanding Plant Panax notoginseng - Huang, Wei; Zhang, Shi-Bao; Liu, Tao (Frontiers in Plant Science, 2018)
Although photoinhibition of photosystem II (PSII) frequently occurs under natural growing conditions, knowledge about the effect of moderate photoinhibition on linear electron flow (LEF) remains controversial. Furthermore, mechanisms underlying the decrease in LEF upon PSII photoinhibition are not well clarified. We examined how selective PSII photoinhibition influenced LEF in the attached leaves of shade-demanding plant Panax notoginseng. After leaves were exposed to a high level of light (2258 μmol photons m-2 s-1) for 30 and 60 min, the maximum quantum yield of PSII (Fv/Fm) decreased by 17% and 23%, respectively, whereas the maximum photo-oxidizable P700 (Pm) remained stable. Therefore, this species displayed selective PSII photodamage under strong illumination. After these treatments, LEF was significantly decreased under all light levels but acidification of the thylakoid lumen changed only slightly. Furthermore, the decrease in LEF under low light was positively correlated with the extent of PSII photoinhibition. Thus, the decline in LEF was not caused by the enhancement of lumenal acidification, but was induced by a decrease in PSII activity. These results indicate that residual PSII activity is an important determinant of LEF in this shade-adapted species, and they provide new insight into how strong illumination affects the growth of shade-demanding plants.